Experimental research of hydrodynamic pulsator and its influence on parameters of oil - Якимечко, Ярослав Яремович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper describes an improved design of a hydrodynamic pulsator, which is used in a technological scheme when pulling high-viscosity oils from wells to the surface. Also, a scheme of performing laboratory tests on the hydrodynamic pulsator is presented. The obtained results indicate that when using this device, physical fields i.e. ultrasound, thermal and cavitation, which help to reduce oil viscosity and increase its temperature, appear in the Kohanowski field’s oil. It is experimentally determined that under the acoustic field (ultrasound) action, fleeting pressure gradients appear and boundary layers of the fluid are destructed, a non-Newtonian fluid is transmitted to Newtonian. At a certain field intensity (more than 0.1 kW/m2) over 50% of acoustic energy is transformed into heat. Thus, while oil is simultaneously exposed by thermal (thermo-acoustic effect) and acoustic (ultrasound) fields. In a high-intensity acoustic (ultrasound) field, there are so-called gravitational effects, which lead to a loss of mechanical impurities, solid paraffin and salts.